EVALUASI PENGENDALIAN INTERNAL SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS PADA PT. HASJRAT ABADI CABANG MALALAYANG MANADO - Kalumata, Novita; Nangoi, Grace B.; Lambey, Robert (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Internal Control Accounting Information System serves to maintain the company's wealth to check the accuracy and reliability of accounting data financial statements, encourage efficiency, and encourage compliance with management policies. Improper sales and cash receipts management will be detrimental to the company. Therefore, companies need the internal control of accounting information system sales and cash receipts in order to reduce the possibility of fraud, waste, ineffectiveness and inefficiency that can harm the company. The purpose of this study is to evaluate the internal control of accounting information systems sales and cash receipts at PT. Hasjrat Abadi Malalayang Manado Branch. This research uses a descriptive method. The results Show that the internal control of accounting information systems sales and cash receipts at PT. Hasjrat Abadi Malalayang Branch Manado is appropriate, it is seen from the implementation of elements of internal control is adequate and adequate supported by policies and procedures of sales and cash receipt is good in accordance with the theory of COSO.Keywords: Internal Control of Accounting Information System, Sales and Cash Receipts